Numerical and experimental investigation of a novel waveguide design for use in high power laser diode devices - Patchell, John A. (Trinity College (Dublin, Ireland). School of Physics, 2002)
Because of their efficiency, small size and reliability high power laser diodes are used for numerous tasks, such as the pumping of solid state lasers, second harmonic generation and the pumping of rare earth fibre amplifiers. The next generation of optical networks will most likely use Raman amplifiers for optical regeneration instead of Erbium doped fibre amplifiers. Up to now the widespread use of Raman has been limited by the availability high power pump modules. In this thesis we examine a new type of waveguide design for use in high power laser diodes, a unique feature of this design is that the last mode before cut-off is predominantly confined to the low index region of the waveguide structure. As this is quite a counter intuitive result, structures based on this design concept, are for shorthand purposes referred to as Lo-guides. The subject matter in this thesis is concerned with the investigation of waveguide structures which could potentially facilitate the production of higher power single spatial mode laser diodes.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin